Once upon a time in Hollywood [compact disc] : original motion picture soundtrack. - Sainte-Marie, Buffy; Diamond, Neil; Feliciano, José, 1945-; Tarantino, Quentin; Jarre, Maurice (Columbia, 2019)
Personally curated by Quentin Tarantino himself, this soundtrack is a love letter to the music of 1960s-era Hollywood. Featuring over 20 standout tracks from artists such as Paul Revere & The Raiders, Deep Purple and Neil Diamond, the album creates a true time capsule of a golden era of filmmaking.